2010
DOI: 10.1111/j.1742-7843.2010.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medication on Microvascular Vasodilatation in Patients with Systemic Lupus Erythematosus

Abstract: The aim of this study was to investigate the microvascular responses in the skin, to local heat, iontophoretically administered acetylcholine and to sodium nitroprusside in relation to cardiovascular damage in patients with systemic lupus erythematosus (SLE) and matched controls. We also wanted to examine if the ongoing medication in SLE patients influenced this vascular response. We investigated 30 women with SLE and compared them with 20 age and sex-matched controls. The cutaneous blood flow response to loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…[47][48][49] However, the cutaneous microvascular reactivity to local heat or iontophoretically administered acetylcholine did not differ between patients with SLE and matched controls. 50 However, in NZBWF1 mice, which have uniform genetics and environmental conditions, we found impaired aortic endothelium-dependent relaxation response to acetylcholine. Interestingly, Ryan and McLemore 51 found that the impaired response to acetylcholine begins before the development of proteinuria and increased blood pressure, suggesting that early changes in vessel function may contribute to the development of hypertension during SLE.…”
Section: Discussionmentioning
confidence: 72%
“…[47][48][49] However, the cutaneous microvascular reactivity to local heat or iontophoretically administered acetylcholine did not differ between patients with SLE and matched controls. 50 However, in NZBWF1 mice, which have uniform genetics and environmental conditions, we found impaired aortic endothelium-dependent relaxation response to acetylcholine. Interestingly, Ryan and McLemore 51 found that the impaired response to acetylcholine begins before the development of proteinuria and increased blood pressure, suggesting that early changes in vessel function may contribute to the development of hypertension during SLE.…”
Section: Discussionmentioning
confidence: 72%
“…However, a different study in Chinese SLE patients did not show significant effect on serum lipid profile, but these patients had mild or absent disease-activity and used low corticosteroid dose [53]. Of note, in addition to its metabolic effects on blood sugar and lipids, HCQ was recently also shown to improve endothelial function and to protect against thrombovascular events in lupus patients [54][55][56].…”
Section: Metabolic and Cardiovascular Effectsmentioning
confidence: 99%
“…Antimalarials have been found to increase endothelium‐dependent vasodilatation 37 . One study has shown a significantly lower prevalence of vascular stiffness in premenopausal women with SLE treated with hydroxychloroquine 38 .…”
Section: Mechanisms Of Actionmentioning
confidence: 99%